ANALYZE ACUTE PARAPROCTITIS - Bobokulov A.U; Usmonkulov M.K; Babakulova F.U; Toxirova V.Y. (Journal of Medical Genetics and Clinical Biology, 2024)
One of the most common diseases in emergency proctology is acute paraproctitis, the incidence of which, according to our data, occupies a leading position in the structure of proctological diseases. Acute paraproctitis is the most complex form of purulent inflammatory processes. According to the literature, patients with acute paraproctitis make up 0.5-4% of people with general surgical pathology and 20-40% of the structure of proctological diseases. The number of these patients and the increasing resistance of microbes require the development of more effective treatments.